Extending Siena to support more expressive and flexible subscriptions - LEWIS, DAVID; O'SULLIVAN, DECLAN; KEENEY, JOHN; JONES, DOMINIC HUGH (My University, 2008)
This paper defines and discusses the implementation of two novel extensions to the Siena Content-based Network (CBN) to extend it to become a Knowledge-based Network (KBN) thereby increasing the expressiveness and flexibility of its publications and subscription. One extension provides ontological concepts as an additional message attribute type, onto which subsumption relationships, equivalence, type queries and arbitrary ontological subscription filters can be applied. The second extension provides for a bag type to be used that allows bag equivalence, sub-bag and super-bag relationships to be used in subscription filters, possibly composed with any of the Siena subscription operators or the ontological operators previously mentioned. The performance of this KBN implementation has also been explored. However, to maintain scalability and performance it is important that these extensions do not break Siena?s subscription aggregation algorithm. We also introduce the necessary covering relationships for the new types and operators and examine the subscription matching overhead resulting from these new types and operators.
The 2nd International Conference on Distributed Event-Based Systems
PUBLISHED
Rome, Italy.
Keywords: publish-subscribe; content-based networks; knowledge-based networks; ontologies; semantics; bags